Moments of Characteristic Polynomials Enumerate Two-Rowed Lexicographic Arrays - Strahov, E. (The Electronic Journal of Combinatorics, 2003)
A combinatorial interpretation is provided for the moments of characteristic polynomials of random unitary matrices. This leads to a rather unexpected consequence of the Keating and Snaith conjecture: the moments of |ζ(1/2+it)| turn out to be connected with some increasing subsequence problems (such as the last passage percolation problem).